If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(l + 4) + -1l + -3 = -4(l + 5) + 5 Reorder the terms: -3(4 + l) + -1l + -3 = -4(l + 5) + 5 (4 * -3 + l * -3) + -1l + -3 = -4(l + 5) + 5 (-12 + -3l) + -1l + -3 = -4(l + 5) + 5 Reorder the terms: -12 + -3 + -3l + -1l = -4(l + 5) + 5 Combine like terms: -12 + -3 = -15 -15 + -3l + -1l = -4(l + 5) + 5 Combine like terms: -3l + -1l = -4l -15 + -4l = -4(l + 5) + 5 Reorder the terms: -15 + -4l = -4(5 + l) + 5 -15 + -4l = (5 * -4 + l * -4) + 5 -15 + -4l = (-20 + -4l) + 5 Reorder the terms: -15 + -4l = -20 + 5 + -4l Combine like terms: -20 + 5 = -15 -15 + -4l = -15 + -4l Add '15' to each side of the equation. -15 + 15 + -4l = -15 + 15 + -4l Combine like terms: -15 + 15 = 0 0 + -4l = -15 + 15 + -4l -4l = -15 + 15 + -4l Combine like terms: -15 + 15 = 0 -4l = 0 + -4l -4l = -4l Add '4l' to each side of the equation. -4l + 4l = -4l + 4l Combine like terms: -4l + 4l = 0 0 = -4l + 4l Combine like terms: -4l + 4l = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 0.8x-0.4(60+x)=0.067(60) | | 0.18y+0.03(y+6000)=810 | | (2x+2)=-4 | | 16x^7-x^3-65= | | 3/4÷2= | | 6(2/3-3) | | 14x-2(2x-4)=9x+9 | | 4x^4+12x^7=0 | | X+100=-235 | | 8.3x+5=9.7x-1 | | 121x^2-324= | | -9/-3*2/-5*8 | | x+x-28=152 | | -5/6t=15 | | y=2x^2+12x-39 | | 9a^3-5a^3= | | (x^4-25)(x^2-1)=0 | | 0.05*(x^90)=5 | | 12x+3=18x-3 | | 27w/-12w | | 4(m+4)+8(-12m+11)=m-8+8m+11 | | 8(w-84)=88 | | 81=-9(j+87) | | 5(p-65)=85 | | -7(t-9)+2t=-8+t | | 27-m=8 | | 2x/4-1/4=x/3-7/3 | | 4a-11=9+3a | | 5(-6+1)-4n=-5+2n | | 24=-3(t+-24) | | 2(n-52)-22=2 | | 2(t-64)=56 |